The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1080/17458080.2016.1209789
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of heat transfer by water–Al2O3and water–TiO2nanofluids jet impingement in cooling hot steel surface

Abstract: Two different nanofluids, namely waterÀAl 2 O 3 and waterÀTiO 2 , were impinged in the form of jet on hot steel surface to remove high heat flux, and their performance was compared. The dimension of the test steel sample was 120 mm £ 120 mm and 4 mm thickness. Four K-type thermocouples were embedded on the bottom surface of the plate to measure the transient temperature distribution. The time-temperature data were recorded by the help of a data acquisition system (make: CHINO, model: KR2000), and the results w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The convective heat transfer coefficient (h) is the proportionality coefficient between the heat flux (q) and the temperature difference between the surface and the coolant (Ts-Tc). The surface HTC (h) can be calculated from Equation 1 as used by Nayak et al [39].…”
Section: Methodsmentioning
confidence: 99%
“…The convective heat transfer coefficient (h) is the proportionality coefficient between the heat flux (q) and the temperature difference between the surface and the coolant (Ts-Tc). The surface HTC (h) can be calculated from Equation 1 as used by Nayak et al [39].…”
Section: Methodsmentioning
confidence: 99%
“…In the research by Tie et al, 18 they disclose that the augmentation is also observed in case of multiple array jet cooling. In addition to the above, according to Nayak et al, 19 jet cooling performance is more effective if Al 2 O 3 nanoparticles of lower concentration are used. The information and the methodology discussed above still depicts that the achieved quenching rate is not suitable for fast quenching operation, although each parameter variation in the favorable direction of heat transfer shows augmentation.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental data were generated for nanofluids with Al 2 O 3 and TiO 2 nanoparticle weight concentrations of 0.01%, 0.03%, 0.05% and 0.07%. They found that the nanofluid prepared with Al 2 O 3 nanoparticles provided better heat transfer characteristics as compared to that of TiO 2 and DI water [23]. Jaware and Bhagatexperimentally investigated the heat transfer and fluid flow due to the impingement of vertical circular single jet on a horizontal heated surface.…”
Section: Introductionmentioning
confidence: 99%